Diplomasi Publik Sebagai Pendukung Hubungan Indonesia-Malaysia - Tonny Dian Effendi (Jurnal Ilmiah Hubungan Internasional, 2013)
This paper discusses how the role of Public Diplomacy in strengthening Indonesia- Malaysia. This relationship is important because Indonesia-Malaysia relations conflict is very vulnerable and does not rule out the possibility it was caused due to the negative misconception. Opinion of this people in both countries can be one of the factors that influence the second issue of Public Diplomacy of the state. Because it is very important to strengthen understanding and getting to know each other more closely at the community level so it is not easy to be provoked on the issues that can lead to conflict. This paper is divided into four main parts: the problems between Indonesia and Malaysia, the conceptual approach of Public Diplomacy, Public Diplomacy at the Ministry of Foreign Affairs of Indonesia and Malaysia as well as the role that can be played by the Public Diplomacy in strengthening relations between the two states.Bagian the end of this paper is a recommendation to the governments of both countries to optimize the role of public diplomacy.Keywords : Public Diplomacy, Bilateral, Indonesia, Malaysia